2021
DOI: 10.1002/chem.202101796
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of Porous Na3V2(PO4)3 for Sodium‐Ion Storage

Abstract: Na 3 V 2 (PO 4 ) 3 (NVP) has been regarded as a potential cathode material for sodium-ion batteries (SIBs) due to its excellent structural stability and rapid Na + conductivity. However, its electrochemical performances are restricted by the large bulk structure and poor electronic conductivity. The construction of porous NVP materials is a powerful method to improve the electrochemical properties. This concept aims to provide an overview of recent progress of porous NVP materials for SIBs. Herein, the synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…62,63 In the past few years, sporadic reviews have been published, focusing on insights into NVP cathode materials. 14,[64][65][66][67] However, a critical and deep investigation of the limitations, different synthesis parameters, modication strategies, and their effect on the electrochemical performance of NVP is still lacking. Thus, this review presents a summary of the recent progress on NVP materials for use in SIBs, their different synthetic methods together with formation mechanisms, and deep investigation on the various modication approaches (structural modication/tailoring, carbon coating, foreign ion substitution, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…62,63 In the past few years, sporadic reviews have been published, focusing on insights into NVP cathode materials. 14,[64][65][66][67] However, a critical and deep investigation of the limitations, different synthesis parameters, modication strategies, and their effect on the electrochemical performance of NVP is still lacking. Thus, this review presents a summary of the recent progress on NVP materials for use in SIBs, their different synthetic methods together with formation mechanisms, and deep investigation on the various modication approaches (structural modication/tailoring, carbon coating, foreign ion substitution, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Among those materials, NASICON-type Na 3 V 2 (PO 4 ) 3 compound is widely regarded as a potential cathode material for sodium-ion batteries owing to robust structural framework and high electrochemical activity. [18][19][20][21] During charge/discharge, it undergoes a reversible two-electron reaction mechanism based on the V 4 + /V 3 + couple, showing a theoretical capacity of 117 mAh g À 1 and a working potential of 3.4 V (vs Na + /Na). Previous work revealed that carbon-coated Na 3 V 2 (PO 4 ) 3 /C materials could achieve outstanding cycling performance and high-rate capability.…”
Section: Introductionmentioning
confidence: 99%
“…Kinds of transition‐metal oxides, [1–4] Prussian‐blue framework, [5–7] polyanionic compounds, [8–14] and carbonyl organics [15–17] have been investigated as functional electrode materials for fabricating high‐performance sodium‐ion batteries. Among those materials, NASICON‐type Na 3 V 2 (PO 4 ) 3 compound is widely regarded as a potential cathode material for sodium‐ion batteries owing to robust structural framework and high electrochemical activity [18–21] . During charge/discharge, it undergoes a reversible two‐electron reaction mechanism based on the V 4+ /V 3+ couple, showing a theoretical capacity of 117 mAh g −1 and a working potential of 3.4 V ( vs Na + /Na).…”
Section: Introductionmentioning
confidence: 99%